Blood Flow Distribution in Cerebral Arteries. Issue 4 (April 2015) - Zarrinkoob, Laleh; Ambarki, Khalid; Wåhlin, Anders; Birgander, Richard; Eklund, Anders; Malm, Jan
High-resolution phase—contrast magnetic resonance imaging can now assess flow in proximal and distal cerebral arteries. The aim of this study was to describe how total cerebral blood flow (tCBF) is distributed into the vascular tree with regard to age, sex and anatomic variations. Forty-nine healthy young (mean 25 years) and 45 elderly (mean 71 years) individuals were included. Blood flow rate (BFR) in 21 intra- and extracerebral arteries was measured. Total cerebral blood flow was defined as BFR in the internal carotid plus vertebral arteries and mean cerebral perfusion as tCBF/brain volume. Carotid/vertebral distribution was 72%/28% and was not related to age, sex, or brain volume. Total cerebral blood flow (717±123 mL/min) was distributed to each side as follows: middle cerebral artery (MCA), 21%; distal MCA, 6%; anterior cerebral artery (ACA), 12%, distal ACA, 4%; ophthalmic artery, 2%; posterior cerebral artery (PCA), 8%; and 20% to basilar artery. Deviating distributions were observed in subjects with 'fetal' PCA. Blood flow rate in cerebral arteries decreased with increasing age ( P <0.05) but not in extracerebral arteries. Mean cerebral perfusion was higher in women (women: 61±8; men: 55±6 mL/min/100 mL, P <0.001). The study describes a new method to outline the flow profile of the cerebral vascular tree, including reference values, and should be used for grading the collateral flow system.